PERAN SISTEM INFORMASI KESEHATAN BERBASIS ARCGIS DALAM MENDUKUNG EPIDEMIOLOGI PENYAKIT TBC DI SUMATRA BARAT - Vitratul Ilahi; Linda Handayuni; Nia Watri Wahyuni; Jeri Juliandi; Cindy Aulia; Winda Efri Nalza; Ermawati Ermawati; Arini Destri Putri (Ensiklopedia of Journal, 2026)
Tuberculosis (TBC) remains a significant public health problem in Provinsi Sumatera Barat, as the case detection rate and treatment success rate vary across districts and cities. This study aims to examine the role of a health information system based on Geographic Information System (GIS) in supporting the analysis of TBC distribution using 2025 data. The method used is a descriptive approach with spatial (mapping) analysis utilizing ArcGIS to identify the distribution of cases and treatment success rates. The results show that the highest number of TBC cases was found in Kota Bukittinggi (139), followed by Kota Solok (109) and Kota Padang (83). In terms of treatment success, the highest rate was recorded in Solok Selatan (95), while relatively lower success was observed in Kota Pariaman (72). Overall, the total number of TBC case detections in Sumatera Barat reached 1,171, while the treatment success rate was 1,609. The use of GIS helps visualize the spatial distribution of the disease more clearly, making it easier to identify priority areas that require greater attention. In conclusion, GIS-based health information systems play an important role in supporting TBC epidemiological analysis, particularly in mapping, monitoring, and data-driven decision-making. This technology is expected to enhance TBC control efforts to be more effective and evenly distributed across regions. Keywords: Tuberculosis (TBC), Geographic Information System (GIS), Health Information System, Epidemiology, ArcGIS, Provinsi Sumatera Barat